Organizational Corruption Prevention, Internal Audit, and Sustainable Corporate Governance: Evidence from Omani Public Listed Companies - Rehman, Ali (Innovation Journal of Social Sciences and Economic Review, 2022)
This study aims to examine the impact of fraud risk assessment (FRA) and internal audit activity (IA) on sustainable corporate governance (SCG) in publicly listed companies in Oman, through the lenses of Fraud Triangle Theory, Institutional Theory, and Agency Theory. The study also investigates the mediating role of IA between FRA and SCG. A descriptive cross-sectional survey design was employed, targeting members of the board of directors, senior management, and internal audit departments. Data was collected using a web-based application and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that IA has a significant direct impact on SCG and also mediates the relationship between FRA and SCG. However, FRA alone does not show a significant direct effect on SCG. The study concludes that while FRA is essential, its effectiveness in achieving sustainable corporate governance is realized primarily through the activities of internal audit. This research has important implications for regulators and policymakers, suggesting the need for revised corporate governance codes that emphasize the critical role of internal audit in fraud prevention and sustainable governance. Additionally, it highlights the potential for further studies in other Gulf countries and within private companies to validate and extend these findings.
Keywords: Fraud risk assessment; Internal audit activity; Sustainable Corporate governance; Oman